PENGARUH PEMBERIAN KREDIT TERHADAP PROFITABILITAS PERUSAHAAN PADA PT. BANK PEMBANGUNAN DAERAH JAWA BARAT DAN BANTEN, TBK. PERIODE TAHUN 2017-2022 - Syifa, Syifa Sulhah; Euis Hernawati (JEBS (Journal of Economic and Business Student), 2024)
The purpose of this study is to determine the effect of lending on company profitability at PT. Regional Development Bank of West Java and Banten, Tbk. The method used in this study is quantitative analysis and the data used is secondary data in the form of financial statements of PT. Regional Development Bank of West Java and Banten, Tbk. The results of data analysis showed that credit had a very strong relationship with profitability of 0.871 and an effect of 75.8% while the remaining 24.2% was influenced by other variables not involved in this study. There are obstacles that occur, namely the lack of credit distribution, the Covid-19 pandemic factor, and the lack of third party funds. Efforts made to overcome these obstacles include banks carrying out various credit policies with lower interest rates, primarily increasing treasury business activities such as cash management, cash investment, and payment transactions.